Immunotherapy at any line of treatment improves survival in patients with advanced metastatic non‐small cell lung cancer (NSCLC) compared with chemotherapy (Quijote‐CLICaP). Issue 2 (12th December 2019) - Ruiz‐Patiño, Alejandro; Arrieta, Oscar; Cardona, Andrés F.; Martín, Claudio; Raez, Luis E.; Zatarain‐Barrón, Zyanya L.; Barrón, Feliciano; Ricaurte, Luisa; Bravo‐Garzón, María A.; Mas, Luis; Corrales, Luis; Rojas, Leonardo; et al.
Abstract : Background: To compare survival outcomes of patients with advanced or metastatic non‐small cell lung cancer (NSCLC) who received immunotherapy as first‐, second‐ or beyond line, versus matched patients receiving standard chemotherapy with special characterization of hyperprogressors. Methods: A retrospective cohort study of 296 patients with unresectable/metastatic NSCLC treated with either, first‐, second‐, third‐ or fourth‐line of immunotherapy was conducted. A matched comparison with a historical cohort of first‐line chemotherapy and a random forest tree analysis to characterize hyperprogressors was conducted. Results: Median age was 64 years (range 34–90), 40.2% of patients were female. A total of 91.2% of patients had an Eastern Cooperative Oncology Group (ECOG) performance score ≤ 1. Immunotherapy as first‐line was given to 39 patients (13.7%), second‐line to 140 (48.8%), and as third‐line and beyond to 108 (37.6%). Median overall survival was 12.7 months (95% CI 9.67–14 months) and progression‐free survival (PFS) of 4.27 months (95% CI 3.97–5.0). Factors associated with increased survival included treatment with immunotherapy as first‐line ( P  < 0.001), type of response ( P  < 0.001) and PD‐L1 status ( P = 0.0039). Compared with the historical cohort, immunotherapy proved to be superior in terms of OS ( P = 0.05) but not PFS ( P = 0.2). A total of 44 hyperprogressors were documented (19.8%, [95% CI 14.5–25.1%]). Leukocyte count over 5.300 cells/dL was present in both hyperprogressors and long‐term responders. Conclusions: Patients who receive immune‐checkpoint inhibitors as part of their treatment for NSCLC have better overall survival (OS) compared with matched patients treated with standard chemotherapy, regardless of the line of treatment.